KILNS IN ALBANIA: An overview - Shehi, Eduard (Rei Cretariae Romanae Fautorum Acta, 2024)
The archaeological excavations undertaken in Albania since the Second World War have very often offered new evidence for the existence of kilns for pottery as well as for construction materials. The recorded evidence ranges from classical antiquity until the late medieval period. However, the majority of the published sources give evidence for wasters or indirect traces for the presence of kilns. There are only four cases where actual structures of kilns have been found and analyzed but only in two out of four cases is this analytical study accompanied by any illustration.